Incorporating dynamic crop area in hydrological model to address interannual variability in water withdrawal and implication of sustainable water management - Umer, M.; Hanasaki, N.; Gopalan, S. P.; Ali, Zeshan; Oki, T. (Elsevier, 2025)
Water security assessments are critical for policymakers in agriculture-dominated regions, where water demand and withdrawals continuously change due to crop area variations driven by farmers’ decisions. However, hydrological models often assume fixed crop areas, resulting in unrealistic estimates of water demand, withdrawals, and related scarcity. This study investigates the impact of interannual variations in crop areas on agricultural water withdrawals within the Indus River Basin in Pakistan, by incorporating dynamic crop area based on hydro-meteorological factors in the H08 hydrological model. Data analysis revealed a strong lagged correlation between river water availability and crop areas, highlighting river flow as a primary driver of farmers’ crop area decisions, followed by rainfall with a moderate correlation. Based on these findings, three simulation cases were tested for altering crop areas: a fixed crop area case (where crop area remains unchanged), a rain-based case (crop area changes in response to previous years’ rainfall), and a river-based case (crop area changes based on previous years’ river water availability). The results were compared with observed withdrawals, and the river-based case outperformed others across all studied performance indices (MAE, RMSE, R2), highlighting the importance of river flows in incorporating crop area adjustments. Although moderately effective, the rain-based case also captured some interannual variability. In contrast, the fixed crop area case exhibited the weakest performance, emphasizing the need to incorporate dynamic crop area adjustments in hydrological assessments. This approach offers policymakers more accurate assessments to better address water shortages, support sustainable water management, and improve crop planning strategies.